USE OF LEARNING MODELS BASED ON YOUR OWN EXPERIENCE (SELF DIRECTED LEARNING) TO INCREASE STUDENTS' INTEREST IN LEARNING PAI AT MTS BABUL ULUM PAJAK RAMBE MEDAN LABUHAN - Wirianty, Aulia Putri; Hidayat, Rahmat; Sabri, Rijal (Universitas Dharmawangsa, 2022)
This research uses a qualitative method. The aims of this research are, (1) to determine the application of the learning model, (2) to determine interest in learning, (3) to determine the supporting and inhibiting factors, and (4) to determine the evaluation of the use of the self-directed learning model in the subject. PAI at MTs Babul Ulum Tax Rambe Medan Labuhan. The results of this research show that students' interest in using self-directed learning methods at MTs Babul Ulum Tax Rambe Medan Labuhan when studying PAI subjects has gone well. This can be seen in: (1) there is a feeling of joy when following lessons, (2) students are active in asking questions, actively answering questions from the teacher, and actively participating in discussions, (3) there is interest and enthusiasm when participating in class learning, and ( 4) students' attention when listening to the teacher's explanation while teaching. Supporting and inhibiting factors as well as evaluation in the use of self-directed learning methods include factors such as teachers, students and madrasah infrastructure.